2013
DOI: 10.5194/amt-6-917-2013
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of hydrogen cyanide (HCN) and acetylene (C<sub>2</sub>H<sub>2</sub>) from the Infrared Atmospheric Sounding Interferometer (IASI)

Abstract: Abstract. Hydrogen cyanide (HCN) and acetylene (C2H2) are ubiquitous atmospheric trace gases with medium lifetime, which are frequently used as indicators of combustion sources and as tracers for atmospheric transport and chemistry. Because of their weak infrared absorption, overlapped by the CO2 Q branch near 720 cm−1, nadir sounders have up to now failed to measure these gases routinely. Taking into account CO2 line mixing, we provide for the first time extensive measurements of HCN and C2H2 total columns at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…It is only slightly perturbed by other weak absorption features of H 2 O and CO 2 . Previous experience has demonstrated that the TIR measurements provide information on the ozone vertical profile from the ground up to an altitude of about 40 km, with a maximum sensitivity located in the mid-troposphere (Worden et al, 2007;Boynard et al, 2009;Dufour et al, 2012). The density of the spectra makes it difficult to discriminate individual lines and hence information in the boundary layer can hardly be obtained.…”
Section: Sensitivity Of Iasi and Iasi-ng Channels To Ozonementioning
confidence: 99%
“…It is only slightly perturbed by other weak absorption features of H 2 O and CO 2 . Previous experience has demonstrated that the TIR measurements provide information on the ozone vertical profile from the ground up to an altitude of about 40 km, with a maximum sensitivity located in the mid-troposphere (Worden et al, 2007;Boynard et al, 2009;Dufour et al, 2012). The density of the spectra makes it difficult to discriminate individual lines and hence information in the boundary layer can hardly be obtained.…”
Section: Sensitivity Of Iasi and Iasi-ng Channels To Ozonementioning
confidence: 99%
“…in a specific biomass burning plume (Clarisse et al, 2011a), as well as in an anthropogenic pollution plume uplifted in the free troposphere (Clarisse et al, 2011b). More recently, Duflot et al (2013) have shown that HCN and C 2 H 2 columns can be routinely retrieved from IASI spectra, even in the absence of exceptional columns or uplift mechanisms, when CO 2 line mixing is accounted for in the inversion scheme. These previous works were based on an optimal estimation method (OEM) developed and formalized by Rodgers (2000).…”
Section: Introductionmentioning
confidence: 98%
“…This gives the stability thresholds above which HCN column amount can be measured with a 10 % confidence in the independence of the retrieval method to the atmospheric parameters. Consequently, as the stability thresholds of the method for HCN in temperate and polar atmospheres are too high (1.2 and 1.6 × 10 16 molec cm −2 , respectively) to allow for the detection of HCN background abundances as compared to usual background column of typically 0.35 × 10 16 molec cm −2 (Vigouroux et al, 2012;Duflot et al, 2013), IASI HCN measurements have to be rejected in these two types of atmosphere, and considered in the tropical belt for values above 0.28 × 10 16 molec cm −2 . In order to broaden the exploitable latitude range, we performed the same study for subtropical latitudes (considering a mix of tropical and temperate atmospheres), and we found a 25 % confidence in the independence of the retrieval method to the atmospheric parameters (data not shown).…”
Section: Sensitivity and Stability Of The Methodsmentioning
confidence: 99%
See 2 more Smart Citations